Musculoskeletal disorders in construction: A review and a novel system for activity tracking with body area network. (May 2016) - Valero, Enrique; Sivanathan, Aparajithan; Bosché, Frédéric; Abdel-Wahab, Mohamed
Abstract: Human body motions have been analysed for decades with a view on enhancing occupational well-being and performance of workers. On-going progresses in miniaturised wearable sensors are set to revolutionise biomechanical analysis by providing accurate and real-time quantitative motion data. The construction industry has a poor record of occupational health, in particular with regard to work-related musculoskeletal disorders (WMSDs). In this article, we therefore focus on the study of human body motions that could cause WMSDs in construction-related activities. We first present an in-depth review of existing assessment frameworks used in practice for the evaluation of human body motion. Subsequently different methods for measuring working postures and motions are reviewed and compared, pointing out the technological developments, limitations and gaps; Inertial Measurement Units (IMUs) are particularly investigated. Finally, we introduce a new system to detect and characterise unsafe postures of construction workers based on the measurement of motion data from wearable wireless IMUs integrated in a body area network. The potential of this system is demonstrated through experiments conducts in a laboratory as well as in a college with actual construction trade trainees. Highlights: We present a review of assessment frameworks used for the evaluation of body motion. Different methods for measuring working postures and motions are compared. We introduce a new system to characterise unsafe postures of construction workers.